Coeficientes de Hilbert e profundidade de anéis graduados associados - Maciel, Tuanny da Silva (2014)
Our goal in this work is to present beautiful results due to Huckaba-Marley concerning the Hilbert coefficients of an ideal of finite co-length in a Cohen-Macaulay local ring, as well as the depth of its associated graded ring. For this end, we employ the Huckaba- Marley complex, which is a fundamental tool for the obtainment of the main theorem discussed herein.